Miniaturisation of high-throughput plasmid DNA library preparation for next-generation sequencing using multifactorial optimisation - Lorna Suckling; Ciaran McFarlane; Chelsea Sawyer; Stephen P. Chambers; Richard I. Kitney; David W. McClymont; Paul S. Freemont (Synthetic and Systems Biotechnology, 2019)
High-throughput preparation of plasmid DNA libraries for next-generation sequencing (NGS) is an important capability for molecular biology laboratories. In particular, it is an essential quality control (QC) check when large numbers of plasmid variants are being generated. Here, we describe the use of the Design of Experiments (DOE) methodology to optimise the miniaturised preparation of plasmid DNA libraries for NGS, using the Illumina® Nextera XT technology and the Labcyte Echo® acoustic liquid dispensing system. Furthermore, we describe methods which can be implemented as a QC check for identifying the presence of genomic DNA (gDNA) in plasmid DNA samples and the subsequent shearing of the gDNA, which otherwise prevents the acoustic transfer of plasmid DNA. This workflow enables the preparation of plasmid DNA libraries which yield high-quality sequencing data.